Mathematics Connections Based on Self Regulated Learning Through Project Based Learning with Ethnomathematics nuances and independent learning with assisted of Module and Whatsapp - Fathonah, Ika Ariwanti; Mariani, Scolastika; Sukestiyarno, YL (Unnes Journal of Mathematics Education Research, 2021)
The study aims to describe the mathematical connections ability in project based learning nuanced ethnomatematic and independent learning module-assisted and whatsapp in terms of self-regulated learning. This study uses a mixed method with explanatory sequential design. Subjects of this study were 7th grade students of SMP Negeri 1 Bae Kudus 2018/2019 school year. The subjects in this study were students of class VIIF and VIIG selected based on three categories of self regulated learning, namely high, medium, and low. Data collection techniques using tests of students' mathematical connection ability, self regulated learning questionnaire, observation of self regulated learning and interviews. The results showed that the project-based learning nuanced ethnomatematics and independent learning with modules and whatsapp was effective against mathematical connection ability, and the description of the ability of mathematical connections in terms of self regulated learning in the high, medium, and low learning in the project-based learning nuanced ethnomatematics and independent learning with modules and whatsapp gets varied results.